Physician-Researchers’ Experiences of the consent process in the sociocultural context of a developing country - Malik, A (Taylor and Francis, 2011)
Background: International guidelines for medical research involving human subjects maintain the primacy of informed consent while recognizing cultural diversity. Methods: This article draws on empirical data obtained from interviews with physician-researchers in teaching hospitals of Lahore, Pakistan, to identify social and cultural factors that affect the consent process for participants in research. Results: This article presents variable findings with regards to communication, comprehension, and decision making. While some physicians consider that social factors such as lack of education, a patriarchal family system, and skepticism about research can make patients dependent on either the physician-researcher or the family, others believe that patients do make independent decisions. Conclusions: In light of the findings, the article ends with a recommendation for communication and decision making that is sensitive to the local sociocultural environment while at the same time meeting the ethical imperative of respect for persons.